Critical Dietary Factors in Cancer Chemoprevention 2016
DOI: 10.1007/978-3-319-21461-0_5
|View full text |Cite
|
Sign up to set email alerts
|

The Ketogenic Diet as an Adjuvant Therapy for Brain Tumors and Other Cancers

Abstract: Altered metabolism was first identified in cancer cells by Otto Warburg, who identified a higher reliance on anaerobic glycolysis rather than cellular respiration even in the presence of sufficient oxygen levels, a phenomenon called the Warburg Effect. Deregulated metabolism is now considered a driving hallmark of cancer and an attractive therapeutic target. While a great deal of work is being done to find genetic therapeutic targets that can be used for personalized medicine, current targeted approaches are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 127 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…The commonly accepted mechanism by which the ketogenic diet may aid in cancer therapy is that the lowering of circulating glucose, and the inability of tumors to use ketone bodies, results in reduced tumor growth or tumor regression. 80,81 Whilst this theory remains the most accepted explanation for a mechanism of the ketogenic diet, several studies have suggested that the effect on tumor growth may not be solely via a decrease in glucose levels. 9,12,82 Indeed, many tumors preferentially use glutamine as a substrate rather than glucose but whether a ketogenic diet has any effect on such tumors is unknown.…”
Section: Cancermentioning
confidence: 99%
“…The commonly accepted mechanism by which the ketogenic diet may aid in cancer therapy is that the lowering of circulating glucose, and the inability of tumors to use ketone bodies, results in reduced tumor growth or tumor regression. 80,81 Whilst this theory remains the most accepted explanation for a mechanism of the ketogenic diet, several studies have suggested that the effect on tumor growth may not be solely via a decrease in glucose levels. 9,12,82 Indeed, many tumors preferentially use glutamine as a substrate rather than glucose but whether a ketogenic diet has any effect on such tumors is unknown.…”
Section: Cancermentioning
confidence: 99%
“…Following the screening of titles and abstracts, 19 remained eligible for inclusion. These studies underwent a full text review, following which a further 13 studies were excluded due to inappropriate interventions [ 10 , 11 ], inappropriate populations [ 7 , 12–15 ] and inappropriate outcome measures [ 16–20 ]. Therefore six studies met the eligibility criteria for this review ( Figure 1 ) [ 21–26 ].…”
Section: Resultsmentioning
confidence: 99%